A 30 days’ postoperative complications after Gynecologic surgery at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A Retrospective cohort study - ABUYE, BINYAM ESAYAS; Dawit Desalegn; Esayas Berhanu; Husnia Hussen; Yirgu G/HIwot (Ethiopian Journal of Reproductive Health, 2025)
Background: Postoperative complications are defined as any deviation from the normal postoperative course (1). The incidence of these complications after elective surgery in low- and middle-income countries is estimated at 11% (2). However, studies show that the 30-day postoperative complication rate following gynecologic surgery can vary significantly, ranging from 0.2% to 26% (3,4,5,6). To date, no studies have specifically examined postoperative complication rates following Gynecologic Oncology surgery in Ethiopia. This retrospective study aims to investigate postoperative complications to enhance patient care. Objectives: To assess 30-day postoperative complications following gynecologic surgery at Tikur Anbessa Specialized Hospital (TASH) in Addis Ababa, Ethiopia, in 2024 G.C. Methods: We conducted a retrospective cohort study examining 30-day postoperative complications among gynecologic surgical patients over three years, from January 2021 to December 2023 G.C. After obtaining ethical clearance from the Departmental Research and Publication Committee (DRPC), we compared categorical variables using the chi-square test. Both binary and multiple logistic regressions were performed to identify associated factors, with significance set at P < 0.05 and a 95% confidence interval (CI). Results: A total of 355 patients who underwent gynecologic surgery were analyzed during the study period. Of these, 118 patients were presumed to have benign conditions, while 237 were diagnosed with malignancies preoperatively. Patients undergoing surgeries for oncological indications were significantly older, with a median age of 48 years (IQR 40-60), compared to a median age of 37 years (IQR 30-45) for benign cases. The overall postoperative complication rate was 31%, with 41% of histopathology-confirmed malignant patients experiencing complications, compared to 19.6% of confirmed benign cases. The most common complication among benign surgical patients was surgical site infection (SSI), while intraoperative or postoperative blood transfusion was the primary complication for malignant patients, followed by SSI. Overall, 16% (58/355) of patients required intraoperative transfusions, with rates of 8.3% in benign cases and 23.5% in oncologic cases. Postoperative readmission rates were 2.4% for benign cases and 6.4% for malignant cases, with SSI being the leading cause of readmission. Multivariable analysis identified that being underweight (AOR 3.829, 95% CI 1.396-10.506), overweight (AOR 1.731, 95% CI 1.019-2.941), and a postoperative diagnosis of malignancy (AOR 3.234, 95% CI 1.958-5.343) were significantly associated with complications. Conclusion: This study demonstrates that postoperative complications are not uncommon following gynecologic oncologic surgeries, with a mortality rate of 1.6% among confirmed malignant cases. The most frequent complication in malignant cases was intraoperative or postoperative blood transfusion, and the postoperative readmission rate was nearly threefold higher in malignant cases compared to benign cases. This comprehensive data on complications can inform future benchmarking of surgical practices.